(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the nutritional status of children under 24 months of age who come for vaccination and to study some factors related to the nutritional status of the study subjects. Research methods: A cross-sectional descriptive study was conducted on 419 children under 24 months of age and their mothers at the vaccination clinic of the Dong Nai provincial Center for Disease Control in 2025. Results: The percentage of underweight, stunting and wasting malnutrition in children under 24 months of age were 3.3%; 5.7% and 4.3%, respectively. There was a relationship between the forms of underweight, stunting and wasting malnutrition in children with the following factors: low maternal BMI, low birth weight, premature birth and early weaning (p < 0.05). Conclusion: Compared to other newborns, premature, low-birth-weight, and early-weaning babies are more likely to suffer from malnutrition. Thus, it is essential to improve nutritional counseling, monitor and care for the fetus for moms, encourage breastfeeding for the first six months, and give proper recommendations for supplemental feeding.